Investigation of changes in blood lactate and some performance characteristics of adolescent male handball players during competition - Mustafa Turkmen (ROL Spor Bilimleri Dergisi)
High lactic acid levels in high-configuration exercises can lead to a decrease in the performance of athletes. The aim of this study is to examine the changes in the characteristics of lactic acid (LA), dominant hand grip strength (DHGS), 20 m sprint and vertical jump (VJ) during the a match. In the study, blood lactate, dominant hand power, vertical power and 20 m sprint values were determined from the subjects, which were taken three times in total, at the end of the warm-up, before the start of the match, at the end of the first half and end of the match. 22 male handball players aged 12-14, playing in the U16 Handball League in 2022-2023, voluntarily participated in this research. The mean age of the subjects was 14,09±0,86 years, and the mean age of sports was 4,04±0,84 years. One-Way ANOVA was performed to analyze the difference. In our study, when the analysis results of lactic acid measurement and DHGS measurements are examined, it is seen that there is a statistically significant difference between pre-competition measurement (PrCM) and half-time measurement (HTM), PrCM and post-competition measurement (PoCM), HTM and PrCM (P <0.05). In addition, when the VJ measurement analysis results are examined, there is a statistically significant difference between PrCM and PoCM, HTM and PoCM results, and between PrCM and HTM, PrCM and PoCM results in the 20 m sprint test (P<0.05). There is an increase in the level of lactic acid in adolescent handball players during the competition, which negatively affects the performance of the athletes.